Matricellular proteins as possible biomarkers for early brain injury after aneurysmal subarachnoid hemorrhage - Suzuki, Hidenori (Neural Regen Res, 2018)
Aneurysmal subarachnoid hemorrhage remains devastating, and the most important determinant of poor outcome is early brain injury (EBI). In clinical settings, as a surrogate marker of EBI, loss of consciousness at ictus, poor initial clinical grades, and some radiographic findings are used, but these markers are somewhat subjective. Thus, it is imperative to find biomarkers of EBI that have beneficial prognostic and therapeutic implications. In our opinion, an ideal biomarker is a molecule that is implicated in the pathogenesis of both EBI and subsequently developing delayed cerebral ischemia (DCI), being a therapeutic target, and can be measured easily in the peripheral blood in an acute stage. A good candidate of such a biomarker is a matricellular protein, which is a secreted, inducible and multifunctional extracellular matrix protein. There are many kinds of matricellular proteins reported, but only tenascin-C, osteopontin, galectin-3 and periostin are reported relevant to EBI and DCI. Reliable biomarkers of EBI may stratify aneurysmal subarachnoid hemorrhage patients into categories of risk to develop DCI, and allow objective monitoring of the response to treatment for EBI and earlier diagnosis of DCI. This review emphasizes that further investigation of matricellular proteins as an avenue for biomarker discovery is warranted.